Comprehensive Review of Advancements in Pharmaceutical Care and Practice - Alwasi, Abdullah Ali; Albalawi, Abdulaziz Saleh; Hamoud, Alkbsani Sultan; Albalawi, Sami Basheer; Khalawi, Ahmed Ali; alsurayyie, Majed Mohammed; Mohammed, Alshehri Khalid; Alharbi, Majed Rabeh; ALshrari, Abdulrahman Dhabayan; Albalawi, Ziyad Mohammed Ali (Journal of Ecohumanism, 2024)
Pharmaceutical care as an ameliorative science has progressed over the past decades from the mechanical concept of medicine distribution to a more enhanced patient-centered systematic procedure incorporating outcomes of therapeutics, medication precautions, and pharmacists as a component of patient care. As such, the following extensive literature review reviews relevant literature to categorize advancements in pharmaceutical care and practice and the existing issues and advancements in the field. Specific topics include the development and future of the new individualized approach in medicine, the fate of pharmacists in condition and chronic disease management using digital health technologies, and ideas for enhancing medication therapy. This review also discusses the implications of these developments on patient outcomes, cost, and efficiency of the health system. This study underscores the importance of leadership by pharmacists and advocacy for equal access of patients to drugs irrespective of their social status, compliance with recommended schedules, and other ways of increasing the effectiveness of the medication. Consequently, the review concludes by advancing recommendations aimed at improving the future of pharmaceutical care by conducting future research, adopting better policies, and providing better training to the practitioners.